A civil society watchdog for financial markets: where private foundations stand - Thümler, Ekkehard; Fioramonti, Lorenzo (Opendemocracy, 2011)
One might have expected charitable foundations - the financial muscle behind many civil society initiatives - to be keen to support pressure groups or policy research bodies concerned with financial markets structures and players. But the authors have found only weak evidence that foundations really want to engage with the issues and much caution about doing so. The challenge is there, however: formulate a vision and write a plan and the money might, just, be available.